2018
DOI: 10.1097/mpg.0000000000001981
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Outcomes in Children With Liver Diseases

Abstract: More than two-third of included studies showed neurodevelopmental deficits in children with liver diseases, affecting all neurodevelopmental areas. Knowledge on risk factors for impaired neurodevelopment is limited and lack of long-term follow-up is worrying, especially considering the increasing survival rates, resulting in more at-risk patients. Studying early predictors and risk factors of abnormal developmental trajectories of children with liver diseases is indicated to assess strategies to improve their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 46 publications
(177 reference statements)
1
45
0
4
Order By: Relevance
“…In conclusion, our results augment the literature by reporting the long term effects of liver disease experienced in early childhood on cognitive function and associated neurometabolites 5,6,24,28,30 . The exclusionary criteria applied in this study enabled the evaluation of the impact of liver disease and transplantation on cognitive outcomes, independently from associated factors that could also explain these effects.…”
Section: Discussionsupporting
confidence: 76%
“…In conclusion, our results augment the literature by reporting the long term effects of liver disease experienced in early childhood on cognitive function and associated neurometabolites 5,6,24,28,30 . The exclusionary criteria applied in this study enabled the evaluation of the impact of liver disease and transplantation on cognitive outcomes, independently from associated factors that could also explain these effects.…”
Section: Discussionsupporting
confidence: 76%
“…Beside hypertension, atherosclerosis, reduced growth, obesity, lowered bone density, osteoporosis, increased cardiovascular risk factors, and reduced aerobic exercise capacity, a reduced motor development has been reported in these children. [3][4][5][6][7][8][9][10][11] Children with liver diseases are at risk in all neurodevelopmental domains; cognitive, behavioral, and motor outcomes. 11 Although most studies showed impaired motor development in children pre-and post-LTX, 9,10,[12][13][14] one study showed motor scores improved and children reached the norm for their age within 4 years post-LTX.…”
Section: Introductionmentioning
confidence: 99%
“…Given this high survival rate, it is important to focus on the long‐term outcomes. Beside hypertension, atherosclerosis, reduced growth, obesity, lowered bone density, osteoporosis, increased cardiovascular risk factors, and reduced aerobic exercise capacity, a reduced motor development has been reported in these children 3‐11 . Children with liver diseases are at risk in all neurodevelopmental domains; cognitive, behavioral, and motor outcomes 11 …”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, these high survival rates come at the cost of considerable co‐morbidities including hypertension, atherosclerosis, reduced growth, obesity, lowered bone density, osteoporosis, delayed motor development, increased cardiovascular risk factors, and a reduced aerobic exercise capacity . Most of these co‐morbidities are associated with lowered PA .…”
Section: Introductionmentioning
confidence: 99%
“…3 Unfortunately, these high survival rates come at the cost of considerable co-morbidities including hypertension, atherosclerosis, reduced growth, obesity, lowered bone density, osteoporosis, delayed motor development, increased cardiovascular risk factors, and a reduced aerobic exercise capacity. [4][5][6][7][8][9][10][11][12] Most of these co-morbidities are associated with lowered PA. 13,14 Low PA levels and aerobic fitness in childhood are associated with the presence of metabolic syndrome in adolescents after liver transplantation. 15 Several studies were performed to establish that children after liver transplantation have lower PA and aerobic fitness compared to healthy children.…”
Section: Introductionmentioning
confidence: 99%